Karyotypic description and repetitive DNA chromosome mapping of melipona interrupta latreille, 1811 (Hymenoptera: Meliponini) - Travenzoli, Natália Martins; Barbosa, Ingrid Cândido de Oliveira; Carvalho-zilse, Gislene Almeida; Salomão, Tânia Maria Fernandes; Lopes, Denilce Meneses (Caryologia, 2019)
Heterochromatic patterns in the genus Melipona vary among subgenera species. Melikerria is the only subgenus that presents species with different content of heterochromatin. Thus, the cytogenetic knowledge of other species of this subgenus is important for the understanding of karyotype evolution in Melipona. Here, we describe the karyotype of Melipona (Melikerria) interrupta based on the chromosomal heterochromatic patterns, AT and GC richness, mapping sequences of rDNA, microsatellites and telomeric regions. We observed 2n=18 chromosomes, with a high heterochromatin content rich in AT and euchromatic regions rich in GC base pairs. The high GC content was observed at interstitial region near the junction of the stained euchromatin and heterochromatin of the first chromosomal pair, the same region marked for the rDNA 18S locus. Microsatellites hybridized only on euchromatin regions and the telomeric probe on terminal regions of all chromosomes. Melipona (Melikerria) interrupta belongs to previous described heterochromatic Group II, suggesting there has been an increase in heterochromatin content in Melikerria. The M. quinquefasciata, belonging to the same subgenus as Melipona (Melikerria) interrupta, has low content of heterochromatin and appears to be evolving independently. So, the differences in the content heterochromatin, in the marker regions of CMA3 and the rDNA 18S locus in species of Melikerria is an important feature to be investigated further. © 2019 N.M. Travenzoli, I.C. de Oliveira Barbosa, G.A. Carvalho-Zilse, T.M.F. Salomão, D.M. Lopes.